ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL CERITA SISTEM PERSAMAAN LINEAR DUA VARIABEL SMP - Fedi Bandara; Halini Halini; Dede Suratman (Jurnal AlphaEuclidEdu, 2022)
Based on the results of the study, in general there are still many students who experience errors in solving problems on the material of a two-variable system of linear equations. The errors experienced by students based on student error indicators are as follows. wrong in choosing a formula or method to solve the problem, wrongly determining the unit of the object in the problem, wrongly writing what to askand know about the difficulty, wrong in using the rules that exist in the elimination and substitution method, wrong perception in interpreting the meaning of the problem. questions, as well as misperceptions between methods of elimination and substitution. While the overall factors causing the error include the following. Factors that come from within students, namely the lack of mastery of the material and lack of interest in mathematics. Factors that come from outside the students are the way the teacher gives lessons.